PENINGKATAN MOTIVASI BELAJAR DAN PEMAHAMAN SISWA MELALUI PEMBELAJARAN GEOMETRI BERBANTUAN PROGRAM KOMPUTER “WINGEOM” PADA POKOK BAHASAN BANGUN DATAR - Novi Mayasari (Jurnal Humaniora, 2016)
This research is a classroom action research (CAR) conducted in order to determine whether (a) increase student motivation in learning geometry (Flat) that uses a computer program medium "Wingeom". (B) to determine an improved understanding of the spatial dimension of students in three media are using the computer program "Wingeom". These results indicate that CTL learning model can improve motivation and increase students' understanding through learning of spatial geometry Computer-aided program "Wingeom" on the subject of class VIII Semester Bangun Datar even in SMP Islam Kedung Bondo Balen Bojonegoro Year 2015/2016.